2015
DOI: 10.3389/fmed.2015.00084
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Dosimetry Studies for Optimization of Pretargeted Radioimmunotherapy in CEA-Expressing Advanced Lung Cancer Patients

Abstract: ObjectivesA phase I pretargeted radioimmunotherapy trial (EudractCT 200800603096) was designed in patients with metastatic lung cancer expressing carcinoembryonic antigen (CEA) to optimize bispecific antibody and labeled peptide doses, as well as the delay between their injections.MethodsThree cohorts of three patients received the anti-CEA × anti-histamine-succinyl-glycine (HSG)-humanized trivalent bispecific antibody (TF2) and the IMP288 bivalent HSG peptide. Patients underwent a pretherapeutic imaging sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…Prepretargeting radioimmunotherapy (pRIT) 111 In-IMP288 immunoscintigraphy showed good tumor targeting with a better contrast when the IMP288 dose was reduced. In our pRIT study assessing the same compounds in lung cancer patients, similar conclusions were reached with regard to the best pretargeting conditions: a pretargeting delay of 24 h, a TF2 dose of 480 nmol/m 2 , and an IMP288 dose of 24 nmol/m 2 (17). However, the constraints for therapy and imaging are different: for therapy, the injected activity must be high, which sets a minimum for the amount of injected IMP288, and the dose to the tumor must be maximum, not necessarily the tumor-to-organ ratios.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Prepretargeting radioimmunotherapy (pRIT) 111 In-IMP288 immunoscintigraphy showed good tumor targeting with a better contrast when the IMP288 dose was reduced. In our pRIT study assessing the same compounds in lung cancer patients, similar conclusions were reached with regard to the best pretargeting conditions: a pretargeting delay of 24 h, a TF2 dose of 480 nmol/m 2 , and an IMP288 dose of 24 nmol/m 2 (17). However, the constraints for therapy and imaging are different: for therapy, the injected activity must be high, which sets a minimum for the amount of injected IMP288, and the dose to the tumor must be maximum, not necessarily the tumor-to-organ ratios.…”
Section: Discussionsupporting
confidence: 70%
“…Pharmacokinetics population modeling was performed using 2-compartment models as described previously (17). …”
Section: Pharmacokinetics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I clinical trial using the dock‐and‐lock technology (anti‐CEA × anti‐histamine‐succinyl‐glycine (HSG)‐humanized trivalent bispecific antibody) for pretargeting against lung cancer was performed to determine dosage of antibody and label. Interestingly, they found that a pretherapy imaging session was good indicator of absorbed doses during therapy sessions . The latest targeting moieties and chemical approaches, however, have demonstrated impressive results in animal models, establishing promise for the eventual application in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they found that a pretherapy imaging session was good indicator of absorbed doses during therapy sessions. 88 The latest targeting moieties and chemical approaches, however, have demonstrated impressive results in animal models, establishing promise for the eventual application in the clinic.…”
Section: Imagingmentioning
confidence: 99%